The mineralisation of fresh and humified soil organic matter by the soil microbial biomass - Brookes, P C (Waste management (New York, N.Y.), 2008)
Soil organic matter comprises all dead plant and animal residues, from the most recent inputs to the most intensively humified. We have found that traces of fresh substrates at microg g(-1) soil concentrations (termed 'trigger molecules') activate the biomass to expend more energy than is contained in the original 'trigger molecules'. In contrast, we suggest that the rate limiting step in soil organic matter mineralisation is independent of microbial activity, but is governed by abiological processes (which we term the Regulatory Gate theory). These two findings have important implications for our understanding of carbon mineralisation in soil, a fundamental process in the sequestration of soil organic matter